University students’ awareness of the social dimension of sustainable transportation: The case of Amasya/Turkey - Sedef Şendoğdu; Ceren Nergiz (PLoS ONE, 2026)
Promoting walking and cycling is crucial for enhancing quality of life and supporting sustainable mobility. Although the literature includes numerous studies addressing the physical and environmental dimensions of sustainable transportation, the social dimension—particularly in relation to bicycle use—has not been sufficiently explored. This gap limits the wider adoption of cycling as a mode of transport. The present study examines university students’ awareness of the social dimension of sustainability, which represents a critical factor in advancing sustainable transportation. Amasya University in Turkey was selected as the case study area due to its diverse academic faculties, the existence of bicycle paths, and the suitability of its urban structure for cycling accessibility. The study aims to reveal how the awareness levels of students from different academic disciplines shape the development of social sustainability in transportation. A mixed-methods approach was adopted, combining attitude analysis, survey applications, and field observations. Attitude analysis was employed to evaluate individuals’ perceptions and behaviors and to explore the extent to which these tendencies can be influenced. The surveys and field observations enabled an integrated evaluation of both quantitative and qualitative data. The findings reveal significant differences in sustainable mobility awareness according to faculty affiliation and socio-demographic characteristics. Female students reported higher bicycle use (60%), while most cyclists belonged to middle- and low-income groups (73.2%). Approximately 47.3% of participants used bicycles for short distances, and 77.4% stated that they cycled primarily for health benefits. In addition, socio-cultural pressures influenced cycling behavior, as 80% of Theology students reported avoiding cycling due to social norms. Overall, the results indicate that indicators such as equity, accessibility, health and safety, individual responsibility, integrated planning, and cultural values and habits play significant roles in shaping students’ awareness and influencing their bicycle use. The study highlights the importance of integrating social dimensions into sustainable transportation policies and university education programs. By doing so, it provides both academic and practical insights for promoting bicycle use and supporting more inclusive and sustainable urban mobility systems.